Letter (copy) : International Solidarity Fund. Help for Spain - Tewson, Vincent
012b-0062-001 Secretary's. HVT/FC/EK/641. S.3/769. 26th January, 1939. Mr. W.J.R. Squance, Associated Society of Locomotive Engineers and Firemen, 9, Arkwright Road, Hampstead, London, N.W.3. Dear Mr. Squance, INTERNATIONAL SOLIDARITY FUND. HELP FOR SPAIN. I have your letter of the 23rd instant and thank you for forwarding a copy of a further letter which you have dispatched to the Prime Minister. Yours sincerely, Assistant Secretary. 292/946/12b/62